2020
DOI: 10.1016/j.ijhydene.2020.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Apparent disagreement between cyclic voltammetry and electrochemical impedance spectroscopy explained by time-domain simulation of constant phase elements

Abstract: A selection of electrodes was analysed using cyclic-voltammetry (CV) and electrochemical impedance spectroscopy (EIS), and a large apparent resistance was observed with CV that was absent with EIS. The explanation for this resistance anomaly was traced to the constant phase element (CPE) behaviour which is exhibited by the electrode double-layer capacitance. Computer simulations of the transient-response of an RQ network (where Q represents a CPE) to a voltage ramp revealed bi-exponential behaviour, with two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…After the deposition of Au NPs, the increased peak current accompanied with a narrowed peak separation proves that the Au NPs are a better electrochemically active material than ITO to improve the performance of the electrode, as echoed by the decreased R et in EIS. , Thereafter, the decrease in the CV peak currents along with greater and greater peak separation was observed after loading of the aptamer and MCH because the macromolecules in the gaps significantly hindered the passage of the probe and the change of the mass-transfer dynamics was fully displayed. Referring to the literature, there may be some substantial discrepancies in the assumptions between both techniques because in CV the system is usually considered to be ideal, whereas in EIS the system is usually considered to be nonideal, or the apparent disagreement between CV and EIS, which can be explained by time-domain simulation of constant-phase elements; the slight deviation from the ideal model attributed to a change of the mass-transfer mechanism of the probe caused by the nanostructured electrode surface in this work can be rationally accepted. These results of CV investigation together with the R et values of EIS, indicated that functionalization of the electrode surface with MSA and Au NPs and the linkage of biomolecules have been successful.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…After the deposition of Au NPs, the increased peak current accompanied with a narrowed peak separation proves that the Au NPs are a better electrochemically active material than ITO to improve the performance of the electrode, as echoed by the decreased R et in EIS. , Thereafter, the decrease in the CV peak currents along with greater and greater peak separation was observed after loading of the aptamer and MCH because the macromolecules in the gaps significantly hindered the passage of the probe and the change of the mass-transfer dynamics was fully displayed. Referring to the literature, there may be some substantial discrepancies in the assumptions between both techniques because in CV the system is usually considered to be ideal, whereas in EIS the system is usually considered to be nonideal, or the apparent disagreement between CV and EIS, which can be explained by time-domain simulation of constant-phase elements; the slight deviation from the ideal model attributed to a change of the mass-transfer mechanism of the probe caused by the nanostructured electrode surface in this work can be rationally accepted. These results of CV investigation together with the R et values of EIS, indicated that functionalization of the electrode surface with MSA and Au NPs and the linkage of biomolecules have been successful.…”
Section: Resultsmentioning
confidence: 84%
“…47,49 Thereafter, the decrease in the CV peak currents along with greater and greater peak separation was observed after loading of the aptamer and MCH because the macromolecules in the gaps significantly hindered the passage of the probe and the change of the mass-transfer dynamics was fully displayed. Referring to the literature, there may be some substantial discrepancies in the assumptions between both techniques because in CV the system is usually considered to be ideal, whereas in EIS the system is usually considered to be nonideal, 50 or the apparent disagreement between CV and EIS, which can be explained by time-domain simulation of constant-phase elements; 51 S6) shows that the sensor exhibits a strong dependence on the saturation of the aptamer loading amount. Moreover, the limiting values of the pulsed electrolytic potential also affect the ECL emission of luminol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This iterative scheme can be converted into a computer program, permitting the simulation of the response of the network to any arbitrary voltage waveform (see SI of Reference [42]).…”
Section: Methodsmentioning
confidence: 99%
“…Neither is it possible to fit an RCR network to the waveform, since this produces a misleadingly high value for the capacitance. This is a result of the constant-phase behaviour of the double-layer capacitance, which not only produces the asymptotic slope, but also alters the curvature of the waveform so that it appears to have a larger time-constant [42]. Therefore the waveform was fitted to an RQ network using the RQ Transient Best-fit method, with the simulation of that network as shown by the dashed blue line in Figure 3b.…”
Section: Raney1mentioning
confidence: 99%
“…(The work on which the remainder of this chapter is based was accepted for publication in the International Journal of Hydrogen Energy in June 2020 [159])…”
Section: Combined Ecsa/eismentioning
confidence: 99%